Development of data correction for the 1M Large Pixel Detector at the EuXFEL. (1st April 2022) - Wheater, R.M.; Hart, M.D.; Veale, M.C.; Wilson, M.D.; Doblas-Jiménez, D.; Turcato, M.; Milne, C.; Yousef, H.; Khakhulin, D.
Abstract: We present the development of a gain correction process for the Large Pixel Detector (LPD) developed by the Science and Technology Facilities Council (STFC) for the Femtosecond X-Ray Experiment (FXE) instrument based at the European X-ray Free Electron Laser (EuXFEL). LPD operates at 4.5 MHz as necessitated by EuXFEL's pulse timing structure and has a large dynamic range capturing a maximum of 10 5 photons/pixel @ 12 keV. Experiments at FXE require highly accurate measurements of relative changes in X-ray scattering intensity on the MHz timescale making a correction bringing LPD pixel outputs in line against a common axis essential to understanding experimental results. To facilitate the operational needs of LPD at FXE more than 1.5 billion correction coefficients are required, with corrections generated on a per pixel, per memory cell and per gain stage basis. By comparing output LPD signals to an independent reference diode a linear gain correction has been developed and applied to LPD data. Improvements in image quality have been quantified using the standard deviation in the measured intensity per pixel for a given radius from the beam centre. Improvements to detector uniformity of up to 30.0% are demonstrated in the medium gain stage and 15.9% in the high gain stage. This paper presents an in-depth view of the gain correction development process and further results.